PENGARUH MOTIVASI, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI UNIT DESA PAKIS KABUPATEN MALANG - Amat Sarbini; Hadi Sunaryo; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis current research aimed to know influence of motivation, diciplin of work, and job satisfaction for the employee’s performance In village unit cooperative of Pakis, Malang regency.This current research was conducted by means of explanatory, motivation research data, dicipline of work, and job satisfaction for the employee’s performance village unit cooperative of Pakis, Malang regency. Sample of this research is all employee’s in village unit cooperative of Pakis, Malang regency. Data collecting through questionnaire. The analysis used is instrument test, normality test, analysis multiple linier regression, classical assumption, hypothesis testing. The results have shown that partially motivation has an important effect on employee performance, work discipline has an important effect on employee performance, and job satisfaction has an important effect on employee performance and simultaneously motivation, work discipline, and job satisfaction have an important effect on employee’s performance in village unit cooperative of Pakis, Pakis district, Malang regency. Keyword. Motivation,  dicipline of work, and job satisfaction.